Jengah dan Transformasi Nilainya - I Putu Sastra Wingarta; Irwan Abdullah; Djoko Suryo (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
Globalization with its threat that continously plaguing Bali, currently a province of Indonesia in its capacity as an island with natural and cultural uniqueness. This study aims to find out, how big a threat that plagued contemporary Bali, and the role of embarrassment (jengah) in the face. The study founds that embarrassment (jengah) with the transformation of the values they contain contribute positively in the face of threat and is able to guarantee the future sustainability of Bali with its uniqueness. By transforming the values of embarrasment (jengah), Bali provincial government managed to improve their good governance and the nationalism of its apparatus, capable of providing a positive impact in the swift efforts to deter threats to the uniqueness of Bali.